Promoting a Coherent Organizational Identity: Identity Work in a Temporary Organization - Juan Liang (SAGE Open)
Threats to organizational identity are particularly salient in temporary organizations because of the tenuous nature of its identity, however, little is known about how organizational identity is created and maintained in such organizations. This paper was developed to address this gap by conducting a qualitative case study at the Stronger Christchurch Infrastructure Rebuild Team (SCIRT), a temporary organization established in the aftermath of the February 2011 Christchurch earthquake in New Zealand. Multiple data sources, including semi-structured interviews, field observations, and organizational documents, were gathered and analyzed using a phronetic iterative approach. The analysis highlights that the definite lifespan of SCIRT necessitates an immediate intervention imperative to prevent identity threats from derailing its operation. The study identified five successive identity work campaigns SCIRT senior managers undertook to counter a series of internal and external threats to its identity and operational success, involving recursive interactions between managers’ sensegiving and employees’ sensemaking of such sensegiving. In particular, it illustrated how a legacy organizational identity emerged during SCIRT’s terminating stage and continued evolving even after its disestablishment. It demonstrates how temporary operation complicates identity work and the development of a legacy identity after the death of an organization. The study contributes an instructive case study to the scant literature on identity work in an increasingly important type of temporary organization.